Ebola virus disease sequelae and viral persistence in animal models: Implications for the future. - Olivia Durant; Andrea Marzi (PLoS Pathogens, 2024)
Ebola virus disease (EVD), caused by infection with Ebola virus, results in severe, acute illness with a high mortality rate. As the incidence of outbreaks of EVD increases and with the development and approval of medical countermeasures (MCMs) against the acute disease, late phases of EVD, including sequelae, recrudescence, and viral persistence, are occuring more frequently and are now a focus of ongoing research. Existing animal disease models recapitulate acute EVD but are not suitable to investigate the mechanisms of these late disease phenomena. Although there are challenges in establishing such a late disease model, the filovirus research community has begun to call for the development of an EBOV persistence model to address late disease concerns. Ultimately, this will aid the development of MCMs against late disease and benefit survivors of future EVD and filovirus outbreaks.